Model Bisnis Media di Era Kecerdasan Buatan (AI): Studi Kasus Transformasi Malang Post - Sao, Wilhelmina; Frida Tri Palupi , Merry; Sigit Pramono , Bambang (KOMUNIKA, 2026)
The media sector has undergone tremendous change as a result of the advent of artificial intelligence (AI), and local media are under pressure as a result of the shift in information consumption habits to the digital sphere. The purpose of this study is to examine how Malang Post's business model has changed in response to the artificial intelligence age and determine how AI may help local media remain sustainable. This study employs a single case study technique and a descriptive qualitative methodology. The findings demonstrate that Malang Post's previous business model has not yet made the best strategic use of AI and still depends on conventional advantages like hyperlocal content, journalistic reputation, and community proximity. AI has not taken the position of humans in terms of originality and journalistic ethics, but it does play a supporting role in increasing the efficiency of content production. Media reputation, local social networks, and preparedness for the digital market are all variables that support change; on the other hand, limited human resources, high technological investment costs, and the lack of digital literacy among advertisers are major barriers. According to the study's findings, the viability of local media in the digital age depends on the thoughtful and prudent integration of AI